The University of the Philippines, 1908-1986 as seen through the presidential papers - Sarmiento, Candida G. (Institute of Library Science, University of the Philippines Diliman, 1993)
This is a historical study which presents a narrative record of each University President's contribution to the historical development of the University of the Philippines from 1908-1986. The study deals on the more important pronouncements of the President of the University, highlights of events that happened during the term of administration.